A Conceptual Study To Evaluate The Effect Of Guduchyadi Basti And Vachadi Upanah In The Management Of Sandhigata Vata W.S.R To Osteo-Arthritis - Meena, Mayank; Bhardwaj, Anil (International Research Journal of Ayurveda & Yoga, 2020)
Introduction – Sandhigata vata, a Vatavyadhi can be compared with Osteo-Arthritis, a degenerative disorder in modern medical science. Most of the degenerative disorders lack effective line of treatment for the prevention and cure of the condition. This research work was conducted with the aim to establish an effective therapy under Panchkarma Chikitsa for the treatment of this disease. Method–In this trial 20 patients of Sandhigata vata were selected from the O.P.D. of Panchakarma Deptt., RGGPG Ayurvedic College & Hospital, Paprola, Dist.- Kangra, H.P. Group-A was treated with Guduchydi Niruh Basti and Ksheera Balataila Anuvasana Basti along with Vachadi Upanah for 16 days. Group-B wastreated with only Guduchyadi Niruh Basti and Ksheera Bala Taila Anuvasana Basti for 16 days. Results – The drugs used in this trial were found significantly effective in all symptoms of the disease except Radiological changes, taken in this trial. Discussion – The disease Sandhigata vata is completely Vatika in nature. The drugs used i.e. Guduchyadi Niruh Basti andVachadi Upanah are potent Vata pacifiers. Basti and Upanaha both are procedure of Panchkarma to pacify Vata. The treatment has shown a significant reduction in the symptoms.